Comparative analysis of morphological traits and photosynthetic parameters as well as carbon accumulation characteristics of six typical shrub species in the Qilian Mountains - Zhou, Rong; Wei, Na; Shangguan, Yaoyao; Zhao, Hu; Chen, Bin; Miao, Yin; Liu, Hongmei; Xie, Xiaobin; Chen, Gang; Zhao, Jingzhong; Lv, Dong (Frontiers in Plant Science, 2026)
IntroductionShrubs are key components of arid ecosystems, and their functional traits directly influence ecological adaptability and productivity. Current research pays insufficient attention to the synergistic relationship between the overall morphological structure and leaf physiological functions of shrubs. This study focused on six typical shrub species in the arid zone of the Qilian Mountains, aiming to analyze interspecific differences in functional strategies from a “morphology–photosynthesis” synergy perspective.MethodsWe selected six typical shrub species (e.g., Cotoneaster multiflorus, Prunus pedunculata, Caragana arborescens, and Lonicera rupicola) and comprehensively measured their morphological traits (plant height, basal diameter, root length, biomass allocation, etc.) and photosynthetic physiological parameters (net photosynthetic rate, transpiration rate, stomatal conductance, etc.).ResultsThe results showed that: (1) Morphologically, C. arborescens exhibited significantly greater plant height (205.17 cm) and whole-plant dry weight (303.03 g), while L. rupicola had deeper root systems (>40 cm); (2) Photosynthetically, the diurnal net photosynthetic rate displayed unimodal and bimodal patterns, primarily driven by photosynthetically active radiation, with L. rupicola and C. arborescens showing the highest estimated daily leaf-level carbon assimilation potential (6.93 and 5.86 g·m⁻²·d⁻¹, respectively); (3) A “scale decoupling” existed between whole-plant carbon storage capacity and leaf-level carbon assimilation potential: C. arborescens had the highest whole-plant carbon storage (120.86 g/plant) but not the highest per-unit-leaf-area assimilation efficiency, whereas L. rupicola exhibited high leaf-level efficiency but moderate whole-plant storage; (4) The six shrubs were classified into three strategic types based on biomass allocation and carbon storage: C. arborescens as “high-accumulation, stem-dominated”; C. multiflorus, Lonicera ferdinandi, P. pedunculata, L. rupicola as “balanced investment”; Euonymus phellomanus as “conservative, belowground-investment”.DiscussionBy integrating leaf-scale carbon assimilation potential estimates with whole-plant carbon storage measurements, this study systematically revealed the scale-decoupling phenomenon and established a more rigorous framework for assessing shrub carbon sinks. The findings demonstrate significant diversity in the synergistic differentiation of morphological and photosynthetic traits as well as carbon accumulation strategies among arid-zone shrubs. Vegetation restoration should select corresponding functional species based on objectives such as rapid carbon accumulation or stress adaptation, providing theoretical support and practical guidance for ecological restoration and carbon sink enhancement in arid regions.